An examination of ISO 9000:2000 and supply chain quality assurance - Sroufe, Robert; Curkovic, Sime (Journal of Operations Management, 2008)
AbstractISO 9000:2000 is the latest version of the quality standard developed by the International Organization for Standardization (ISO). The standard aims to evaluate a firm's ability to effectively design, produce, and deliver quality products and services. This version of the standard tries to enhance customer satisfaction by including more top‐management involvement and continual improvement. Despite widespread international acceptance, the new standard is surrounded by controversy similar to that surrounding its predecessor, the 1994 version. The literature is clearly divided in its assessment of ISO 9000:2000, which is viewed as either a quality management (QM)‐based system or as another paper‐driven process that increases risk, uncertainty, and costs. This study utilizes case‐based research to address the competing views of the ISO 9000:2000 standard in an attempt to see if a sample of firms in the automotive industry can be positioned within the Miles and Snow [Miles, R.E., Snow, C.C., 1978. Organizational Strategy, Structure and Process. McGraw‐Hill, New York] strategic typology. We compare different amounts of quality standard integration and quality assurance in the supply chain of firms with ISO 9000:2000 registration while positing several research propositions.